Virtuoso's milieu promoting learning and development in an outdoor-experience-based educational facility through visual and tactile stimulation - Ugalino, Cris Justine G.; Galingan, Zenaida C.; Dul-loog, Vic L. (Quezon City College of Architecture, University of the Philippines Diliman, 2016)
"There are children playing in the streets who could solve some of my top problems in physics, because they have modes of sensory perception that I lost long ago" -J. Robert Oppenheimer. The prioritization of education and employment in the Philippines, being promoted presently by the government and by the private sector, has still a lot to consider in complementing ways of learning. This is evident in the curricula revised by the government which is applied in the K-12 Basic Education Program (K-12) and the Alternative Learning System (ALS). This study aims to employ experience-based learning for different types of learners (formal, informal and non-formal), and the integration of this to residents of a community: an implementation of community-based planning, which is what the Alternative Learning System is. A small-scale pineapple industry, promoted by the local government and where the community is well-known for, will be the means of sustainability for its accessibility to maintenance, management and development. Piezoelectric pavements will also be used to transduce and generate electricity for aesthetics in visual stimulation and energy generation. Integrating that to the landscape would foster learning outdoors as a factor of learner development, also in the application of design strategies incorporated in the space and place. Developmental psychology and motor development were also considered in the research of this study. The use of the natural wave frequency of our environment, the Schumann resonance, was measured in accordance with the ideal and natural learning state of the environment, which is also effective for learners. Resonances in the environment were considered in the derivation of spaces and while designing to have a low impact on the existing environmental waves (alpha, beta, gamma, delta and theta). Considerations such as economics, business administration, urban and regional planning, developmental psychology and motor development are also present for the viability of the study.
includes appendices
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman